Undergraduates Interested in STEM Research Are Better Students than Their Peers - Nate Bickford; Elizabeth Peterson; Philip Jensen; Dave Thomas (MDPI AG, 2020)
In Science, Technology, Engineering, and Mathematics (STEM), undergraduate research experiences provide students with invaluable opportunities to improve scientific skills. However, less is known about its impact on higher-order thinking skills. Therefore, we sought to determine if engagement in undergraduate research would improve academic performance in students engaged in research compared to those that were not. To accomplish this, biology majors were enrolled in courses that taught research methodology and techniques. Results indicated that students who were selected for the research program outperformed their peers in their other classes during the research program, based on t-test statistics. However, these students had also outperformed their peers during the previous fall semester, prior to receiving additional instruction. Furthermore, students who merely applied for inclusion in the program had significantly higher grades than students who did not apply. In addition, writing samples from research and non-research students were significantly different. Taken together, these data suggest that while undergraduate research may indeed enhance a student's academic performance and interest in science, a student's personal interest and drive for research may themselves indicate superior academic performance. Further, science departments aiming to offer research early in their curricula may benefit from such a self-selection strategy, especially in cases where there are limited resources available for undergraduate research.